2013
DOI: 10.4314/sokjvs.v11i1.4
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of gastric lesions in slaughtered pigs in Ibadan, Nigeria

Abstract: Information about frequency in the occurrence of gastric lesions in pigs slaughtered in Nigeria appears scanty. A random sampling of stomachs of 100 slaughtered pigs from Bodija abattoir, one of the largest abbatoir in south western Nigeria was used for this investigation. The stomachs were examined grossly and the locations of the lesions were noted, tissues were routinely processed and examined histologically. Descriptive statistics and Chi square were employed to analyse data obtained. The predominant lesio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 8 publications
(16 reference statements)
0
8
0
Order By: Relevance
“…The prevalence of gastric lesions in this study was 25.3% as 19 out of the 75 stomachs had visible gross lesions. This included a prevalence of 17.3% (13) in the non-glandular stomach and 21.3% (16) in the glandular stomach ( Table 1). Epithelial changes were restricted to the non-glandular region.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of gastric lesions in this study was 25.3% as 19 out of the 75 stomachs had visible gross lesions. This included a prevalence of 17.3% (13) in the non-glandular stomach and 21.3% (16) in the glandular stomach ( Table 1). Epithelial changes were restricted to the non-glandular region.…”
Section: Resultsmentioning
confidence: 99%
“…The stomach of the pig is characterized by its great fragility, particularly in the pars oesophagea zone close to the cardiac region which increases its susceptibility to lesions (Omotosho et al, 2015). Investigations have shown that gastric lesions including erosions and ulcerations are common conditions in pigs especially in growing pigs than breeding animals in Nigeria (Majekodunmi et al, 2013). Gastric lesions in pigs include ulcerations, lacerations, erosions and epithelial changes.…”
Section: Introductionmentioning
confidence: 99%
“…Research conducted in England by Swaby and Gregory (2012) reported a prevalence of 79.8% of gastroesophageal ulcers of different degrees in 9827 slaughter pigs from 60 farms. Majekodunmi et al (2013) examined stomachs of 100 slaughtered pigs from an abattoir in Nigeria 21 (21%) of them had chronic ulcers. The findings of gastric ulcers reported in Brazil and in other countries are much higher than those obtained in this survey, which the presence of active or chronic ulcer represented 16% (64/400) of the animals (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…This is a problem worldwide. Reports vary, with incidence of pigs showing distinct signs of ulceration between farming operations ranging from zero to nearly 90% [ 32 , 33 , 34 , 35 , 36 ]. For pigs in the growing/finishing stages of production, ulceration is a common cause of mortality [ 37 ].…”
Section: Mitigation Strategies and Possible Negative Animal Welfarmentioning
confidence: 99%